PEMANFAATAN ALAT PERAGA PAPAN PERKALIAN BILANGAN CACAH PADAPEMBELAJARAN MATEMATIKA MATERI PERKALIAN MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA KELAS IV UPTD SDI PERUMNAS 1 - Putri, Alvia Melati; Samo, Damianus Dao; Benu, Adam (SINERGI : Jurnal Riset Ilmiah, 2025)
Utilization of Whole Number Multiplication Board Teaching Aids in Mathematics Learning Multiplication Material Using the Inquiry Learning Model to Improve Student Learning Outcomes in Class IV Uptd Sdi Perumnas 1. The research problem is that learning tends to use the lecture method so that learning is less interesting which causes student learning outcomes to be low. The aim of this research is to improve the learning outcomes of class IV UPTD SDI Perumnas 1 students using the inquiry learning model by utilizing the multiplication board teaching aid. This research method uses the PTK method which consists of 4 stages, namely planning, implementation, observation and reflection. The subjects in this research were class IV B students, totaling 20 students. Data collection techniques are in the form of observation and tests, while the data analysis technique used is quantitative descriptive. The research results showed that in cycle I, the percentage of teacher activity was 64%, the percentage of student activity was 70.50% and the average student test results were 60.5 with a completion percentage of 50%. Meanwhile, in cycle II there was an increase with the percentage of teacher activity being 96%, the percentage of student activity being 80% and the average student test result being 78 with a completion percentage of 80%. Based on the research results obtained, it can be concluded that learning by utilizing multiplication board teaching aids using the inquiry learning model can improve the learning outcomes of class IV UPTD SDI Perumnas 1 students.